Analisis dan Pembuatan Genteng Polimer dengan Memanfaatkan Limbah Karet Industri Serta High Density Polyethylene (HDPE) Bekas - Hafiz Arif Lubis (Saintia Fisika, 2013)
Polymer’s roof has been made using of waste rubber industry and used high density polyethylene (HDPE) in a mixture of asphalt and fine sand. The study was conducted to determine the optimum mixture of HDPE and fine sand used as independent variables with the variation of the composition of 60:15 gr, 55:20 gr, 50:25 gr, 45:30 gr, 40:35 gr, 35:40 gr, 30:45 gr, 25:50 gr, 20:55 gr, 15:60 gr. Then epoxy resin and catalyst was added. Then it pressed on Hot Compressor with heating temperature of 150°C in 15 minutes. Properties of the Polymers’s roof were tested physical properties such as porosity and water absorption, mechanical properties including impact tests, and flexural strength test. The results showed that the mixture a good fit by the experiment is a mixture of used HDPE and fine sand in the ratio 55:20 gr with 5 gr additional asphalt that useful as a barrier against water and 10 gr of epoxy resin as an adhesive.   Key words: Polymer’s roof, waste rubber, high density polyethylene (HDPE)